Identifying cytokine signaling signatures in primary human Th-1 cells by phospho-proteomics analysis - Jonathan Martinez-Fabregas; Elizabeth Pohler; Ignacio Moraga (STAR Protocols, 2021)
Summary: Stable isotope labeling by amino acid-based high-resolution phosphoproteomics is a powerful technique that allows for direct comparison of cells stimulated under different experimental conditions. This feature makes it the ideal methodology to identify cytokine signaling networks. Here, we present an optimized protocol for the isolation and identification of phosphopeptides from IL-6-stimulated primary human Th-1 cells.For complete details on the use and execution of this protocol, please refer to Martinez-Fabregas et al. (2020).